Microwave dielectric properties of pure and Mn‐doped lead‐free Na0.5Bi0.5TiO3 epitaxial thin films grown on (001) LaAlO3 single crystals using pulsed laser deposition. Issue 12 (29th August 2016) - Jean, F.; Huitema, L.; Ghalem, A.; Rammal, M.; Boulle, A.; Rémondière, F.; Orlianges, J.‐C.; Députier, S.; Crunteanu, A.; Passerieux, D.; Chatras, M.; Guilloux‐ Viry, M.; et al.
Abstract : (001)‐epitaxial thin films of pure and Mn‐doped lead‐free Na0.5 Bi0.5 TiO3 (NBT) were grown on (00l) LaAlO3 single crystals, by pulsed laser deposition. The determination of the microwave dielectric permittivity, from interdigitated capacitance values treated using the combination of two previously developed analytical models, constitutes the backbone of this work. In the 3–5 GHz frequency range, constant ϵ r values of ∼485 and ∼515 for the pure and Mn‐doped layers, respectively, were extracted and found in good agreement with literature data for pure NBT bulk ceramics, thus underlining the relevance of the approach. These permittivity values were re‐injected in a second step into an electromagnetic simulation of the equivalent electrical circuit. Smith charts revealed the good matching between experimental and simulated data, proving that the employed method appears meaningful. Mn doping seems to lead to a small permittivity increase and clearly to a moderate reduction of the dielectric losses in the 3–5 GHz interval. Finally, the variation of the capacitance versus temperature testifies to the ferroelectric nature of the samples.